PENINGKATAN KESADARAN GENERASI MUDA TERHADAP RISIKO SELF-DIAGNOSIS KESEHATAN BERBASIS AI - Iswanti Purwaningsih; Hernawan Isnugroho; Pritta Yunitasari; Siti Maryati; Benny Karuniawati; Berlina Putrianti (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2026)
The rapid development of Artificial Intelligence (AI) in healthcare has increased the use of digital platforms for self-health assessment, particularly among young people. However, inadequate understanding of AI may lead to inappropriate self-diagnosis and potential health risks. This community service activity aimed to enhance young people’s awareness of the risks associated with AI-based self-diagnosis through an educative–participatory approach. A pre-experimental design with a one-group pre-test and post-test was employed. The intervention consisted of interactive health education, group discussions, and case-based learning related to AI health applications. Evaluation focused on changes in participants’ knowledge, risk awareness, critical attitudes, and digital health behavior before and after the intervention. The results indicated a significant shift in participants’ perspectives, from uncritical reliance on AI toward more cautious and reflective use. Participants recognized the limitations of AI and the importance of consulting healthcare professionals for medical decisions. This activity supports the development of safer and more responsible health behaviors in the context of increasing AI integration in everyday life in 2026.